Coprinus comatus polysaccharides ameliorated carbon tetrachloride-induced liver fibrosis through modulating inflammation and apoptosis. Issue 21 (7th October 2022) - Zhao, Huajie; Li, Duan; Li, Min; Liu, Liang; Deng, Baoguo; Jia, Le; Yang, Fan
Abstract : Liver fibrosis is a serious global public health problem, owing to a lack of effective treatment. Abstract : Liver fibrosis is a serious global public health problem, owing to a lack of effective treatment. Coprinus comatus polysaccharides (CP), isolated from C. comatus, possess multiple biological activities. In our work, water-soluble polysaccharides (CPa) from CP were obtained by column chromatography. We attempted to investigate the anti-liver fibrosis ability of CPa and the underlying mechanisms of its activity against liver fibrosis in vivo and in vitro, as well as its structure. In vivo results showed that CPa reduced the release of inflammatory factors and apoptosis by modulating the TLR4/MyD88/NF-κB, Bcl-2/Bax and caspase family signaling pathways, thereby attenuating serum enzymes, ROS, α-SMA, collagen III, TGFβ1, p-Smad3, and collagen volume fraction, and increasing the defense capacity of the antioxidant defense system in tetrachloride (CCl4 )-induced liver fibrosis mice. The in vitro result was used to verify that, in vivo, CPa regulated the TLR4/MyD88/NF-κB, Bcl-2/Bax and caspase family signaling pathways to prevent the activation of HSCs and accelerate HSCs apoptosis in activated LX-2 cells. Thus, CPa could attenuate liver fibrosis by mediating inflammation and apoptosis. Meantime, the structural analysis showed that CPa is a polysaccharide with α- and β-configurations including Fuc, Man, Gal and Glc with a M w of 524 kDa. These findings indicate that CPa could be developed into functional foods and drugs against liver fibrosis.